1982
DOI: 10.1007/bf02338973
|View full text |Cite
|
Sign up to set email alerts
|

A clinical trial of fibroblast transplantation for the treatment of mucopolysaccharidoses

Abstract: This paper reports the clinical and biochemical results in six patients with Hurler disease (Mucopolysaccharidosis IH; McKusick 25280), two patients with Hunter disease (Mucopolysaccharidosis II; McKusick 25285) and one patient with Sanfilippo B disease (Mucopolysaccharidosis IIIB; McKusick 25292) who were treated by fibroblast transplantation. Except for one patient who died for a coincidental reason, the patients have been studied for between 2.5 and 4.5 years. The clinical course of the disease was not mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…A moderate shift toward normal in excretion of urinary mucopolysaccharides was also detected, but patients experienced no convincing clinical change. Gibbs et al (1983) also reported that fibroblast transplantation in MPS I, MPS II and MPS III was not therapeutically useful.…”
Section: Ms Receivedmentioning
confidence: 94%
“…A moderate shift toward normal in excretion of urinary mucopolysaccharides was also detected, but patients experienced no convincing clinical change. Gibbs et al (1983) also reported that fibroblast transplantation in MPS I, MPS II and MPS III was not therapeutically useful.…”
Section: Ms Receivedmentioning
confidence: 94%
“…This led to attempts to treat lysosomal storage diseases by systemic cell implantation. An early attempt using cultured histocompatible fibroblasts (Gibbs et al 1983) in some of the mucopolysaccharidoses was unsuccessful. Bone marrow transplantation has been tried on the premise that engrafted bone marrow would produce large numbers of exocytic cells that would circulate and transfer their normal enzyme to enzyme-deficient cells (see Krivit & Paul 1986).…”
Section: Treatment Of the Sphingolipidosesmentioning
confidence: 99%
“…They all looked normal except for the manifestations of disordered motor function. Patients 1 and 2 were given subcutaneous implants of fibroblasts [8] without appreciable overall improvement or deterioration during this period.…”
Section: Patientsmentioning
confidence: 99%